1991
DOI: 10.1021/es00013a020
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and microbial degradation of naphthalene in soil-water suspensions under denitrification conditions

Abstract: The microbial degradation of naphthalene under denitrification conditions in soil-water suspensions was dependent on solute partitioning between soil and water. Soil-associated naphthalene was in equilibrium with aqueous-phase solute, with the rate of naphthalene degradation being mixed order with respect to aqueous concentration. The rate of degradation was modeled by coupling Michaelis-Menten kinetics for aqueous-phase solute with an intraaggregate radial diffusion model for naphthalene sorption and desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 29 publications
8
59
0
Order By: Relevance
“…There are some reports on the direct uptake of hydrophobic substances from surfaces by microorganisms (Guerin and Boyd, 1992;Guerin and Jones, 1988;Hermannson and Marshall, 1985), but generally the desorption or dissolution of PAH to the aqueous phase is considered a prerequisite for biodegradation. The latter view is expressed in most studies and supports the idea that microorganisms can only convert these compounds in the dissolved state (Mihelcic and Luthy, 1991;Scow and Alexander, 1992;Wodzinski and Bertolini, 1972;Wodzinski and Coyle, 1974). Because mass transfer from sorption sites or crystalline surfaces to an aqueous phase with microorganisms is necessary for biodegradation, the physical state of the pollutant in the soil plays an important role (Mihelcic et al, 1993;Rulkens and Bruning, 1995;Wu and Gschwend, 1986).…”
Section: Introductionsupporting
confidence: 57%
“…There are some reports on the direct uptake of hydrophobic substances from surfaces by microorganisms (Guerin and Boyd, 1992;Guerin and Jones, 1988;Hermannson and Marshall, 1985), but generally the desorption or dissolution of PAH to the aqueous phase is considered a prerequisite for biodegradation. The latter view is expressed in most studies and supports the idea that microorganisms can only convert these compounds in the dissolved state (Mihelcic and Luthy, 1991;Scow and Alexander, 1992;Wodzinski and Bertolini, 1972;Wodzinski and Coyle, 1974). Because mass transfer from sorption sites or crystalline surfaces to an aqueous phase with microorganisms is necessary for biodegradation, the physical state of the pollutant in the soil plays an important role (Mihelcic et al, 1993;Rulkens and Bruning, 1995;Wu and Gschwend, 1986).…”
Section: Introductionsupporting
confidence: 57%
“…Various recent investigations have reported on the biodegradation of 2-and 3-ring PAH compounds sorbed on soils (Bauer and Capone, 1988;Mihelcic and Luthy, 1991;Mueller et al, 1991;Park et al, 1990) or present as NAPL components (Efroymson and Alexander, 1994;OrtegaCalvo and Alexander, 1994;Ghoshal et al, 1996;Woodzinski and Larocca, 1977). Laboratory studies employing supersaturated aqueous solutions of PAH compounds have shown that the rates of dissolution control the rates of biodegradation of these compounds (Stucki and Alexander, 1987;Volkering et al, 1993;Woodzinski and Bertolini, 1972;Woodzinski and Coyle, 1974).…”
Section: Bioavailability Of Nonaqueous Phase Pah Compoundsmentioning
confidence: 99%
“…Because dioxygenase enzyme complexes (which require molecular oxygen as a cosubstrate) are essential for the known biochemical mechanisms of naphthalene metabolism [25], one obvious explanation for naphthalene's persistence at the site is simply lack of O 2 . However, anaerobic metabolism of naphthalene under nitrate-reducing conditions has also been reported [26][27][28].…”
Section: Anaerobic Naphthalene Metabolism Assaysmentioning
confidence: 99%
“…Because naphthalene metabolism under denitrifying conditions had been previously reported [26][27][28], an additional attempt using slurried sediments was implemented. The fate of naphthalene in uninoculated, autoclaved, and viable denitrifying treatments is shown in Figure 3.…”
Section: Anaerobic Naphthalene Metabolism Assaysmentioning
confidence: 99%